Using Path Analysis to Evaluate the Healthcare Empowerment Model Among Persons Living with HIV for Antiretroviral Therapy Adherence - van den Berg, Jacob J. (AIDS Patient Care STDS, 2016)
Healthcare empowerment (HCE) is patient controlled and includes the process and state of being engaged, informed, collaborative, committed, and tolerant of uncertainty. Understanding psychosocial factors that impact HCE for persons living with HIV is critical for their treatment and care. A sample of 1494 male and female participants living with HIV in the United States with a mean age of 45.6 (standard deviation = 11.4) completed a one-time online survey about their demographic characteristics, social support, healthcare provider relationship, HIV treatment knowledge, perceived HIV-related stigma, lifetime trauma, depressive symptoms, HCE, and antiretroviral therapy (ART) adherence. A path analysis was conducted using structural equation modeling software to fit a theory-based model of HCE. Results included statistically significant direct pathways between depressive symptoms, healthcare provider relationship, lifetime trauma, and ART adherence, as well as between healthcare provider relationship, HIV treatment knowledge, and HCE. Specifically, ART adherence was positively linked to healthcare provider relationship and negatively linked to depressive symptoms and lifetime trauma. In addition, healthcare provider relationship and HIV treatment knowledge were positively associated with HCE. The indirect effects of healthcare provider relationship and HIV treatment knowledge on adherence through HCE were also significant. In particular, ART adherence was indirectly and positively affected by healthcare provider relationship and HIV treatment knowledge through HCE. Multi-level interventions are urgently needed to address the effects of these psychosocial factors on ART adherence.